Development of a single-tube nested PCR-lateral flow biosensor assay for rapid and accurate detection of Alternaria panax Whetz - Wei, Shuqin; Sun, Yajuan; Xi, Guangsheng; Zhang, Huijuan; Xiao, Mingya; Yin, Rui (PloS one, 2018)
Alternaria panax Whetz causes one of the most commonly occurring and serious diseases in ginseng cultivation, and may cause significant production and economic losses in the ginseng industry. Rapid, early, and accurate identification of Alternaria panax Whetz is an essential prerequisite for the effective prevention and control of further infection spread. In this work, a rapid and accurate molecular diagnostic method, a single-tube nested PCR-lateral flow biosensor assay (STNPCR-LFBA), was developed for rapid identification of Alternaria panax Whetz. The STNPCR-LFBA was 100 times more sensitive than the traditional PCR-LFBA. Besides that, the PCR product was checked by a lateral flow biosensor assay, which provided a basis for the migration of the detection technology to a point-of-care test (POCT) format. STNPCR-LFBA was specific to Alternaria panax Whetz, and no cross-reactions were observed in other non-target samples; the limit of detection was up to 0.01 pg of Alternaria panax Whetz genomic DNA. STNPCR-LFBA could also be used for specific identification of Alternaria panax Whetz in real samples. STNPCR-LFBA is useful for identifying Alternaria panax Whetz due to its rapidity, accuracy, and simple manipulation.